Modeling the process of moisture diffusion by a flameretardant coating for wood - Tsapko, Yu.; Tsapko, A.; Bondarenko, O. (Eastern-European Journal of Enterprise Technologies, 2020)
At present, among the most common building materials is wood, which, in terms of its flammability group, belongs to the group of combustible materials of medium flammability. To reduce these deficiencies, fire-retardant treatment provides wood with the capability to withstand the effects of flame and its propagation. One of the ways to protect wood from fire is to apply a fireproof coating on its surface, which for some time prevents heat from accessing the wood.
Keywords: protective equipment; fire resistance; weight loss; moisture diffusion; surface treatment; protection efficiency; 674.03